2018
DOI: 10.1590/abd1806-4841.20186123
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of Th17 lymphocytes in patients with psoriasis

Abstract: BackgroundPsoriasis is a chronic inflammatory disorder, characterized by increased keratinocyte proliferation due to abnormal differentiation of basal keratinocytes. The etiology of the disease is unclear, and according to the survey results, it is hypothesized that a combination of genetic and environmental factors prompts an abnormal immune response in patients with psoriasis. CD4+ Th cells play a multifaceted role in both immune defense and pathogenesis of certain diseases such as psoriasis. Nonetheless, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
(21 reference statements)
2
11
0
5
Order By: Relevance
“…Another possibility is that Mo-MDSCs downregulate IL-17A levels in circulation [31]. e transcription factor ROR-c plays a critical role in the expression of proinflammatory cytokine IL-17 in patients with psoriasis [32] and is, therefore, an attractive target for the treatment of psoriasis [33]. In the current study, we found the ROR-c mRNA levels were significantly increased in the PBMCs of psoriasis patients when compared to controls.…”
Section: Discussionsupporting
confidence: 52%
“…Another possibility is that Mo-MDSCs downregulate IL-17A levels in circulation [31]. e transcription factor ROR-c plays a critical role in the expression of proinflammatory cytokine IL-17 in patients with psoriasis [32] and is, therefore, an attractive target for the treatment of psoriasis [33]. In the current study, we found the ROR-c mRNA levels were significantly increased in the PBMCs of psoriasis patients when compared to controls.…”
Section: Discussionsupporting
confidence: 52%
“…Data from skin inflammatory models suggest that the Th17 lymphocytes, which produce cytokines IL‐17 and IL‐22, may be the main inducers of the epidermal hyperplasia associated with psoriasis. Cytokines IL‐12 and IL‐23 may also play a significant pathological role in this disease (Mansouri, Mansouri, Raze, & Jadali, ).…”
Section: Introductionmentioning
confidence: 99%
“…Полиморфизм IL17А (rs2275913) довольно активно изучается в отношении ассоциаций развития воспалительных мультифакториальных заболеваний. Так, в некоторых исследованиях не было получено ассоциации IL17А (rs2275913) с ПС и ПсА у поляков [25], а также с другим заболеванием суставов -ревматоидным артритом (РА) у тунисцев, алжирцев, поляков, бразильцев и китайцев [23,27]. В то же время, в других исследованиях показана ассоциация указанного полиморфизма с повышенным риском развития РА у бразильцев и норвежцев [28].…”
Section: Introductionunclassified
“…Ранее была показана ассоциация полиморфизма IL17F (rs763780) с ревматоидным артритом у европеоидов и связанная с этим повышенная концентрация IL-17 в сыворотке крови [23]. В польской популяции не найдена ассоциация IL17F (rs763780) с ПС и ПсА [25].…”
Section: Introductionunclassified
See 1 more Smart Citation